Pendampingan Mahasiswa Program Kampus Mengajar di SD Negeri Guwosari, Pajangan, Bantul, Daerah Istimewa Yogyakarta - Novi Irawati; Hendi Prasetyo; Maria Kurnia Hutabarat (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The Kampus Mengajar program is designed to improve the quality of education in schools that experience limited infrastructure and access to education. The purpose of this activity is to assist students in improving literacy and numeracy, as well as assist teachers in implementing learning technology. The methods used include provisioning and deployment. The results of the activity showed an increase in students' literacy and numeracy skills, as well as an increase in teachers' skills in using technology. In conclusion, this program has a positive impact on students, teachers, and students who participate, and has the potential to improve the quality of education in remote areas.